Descripción de los hallazgos post-mortem en un lobo marino antártico (Arctochepalus gazella) - Gómez, M.V. (2017)
Every year, between November and December, hundreds of Antarctic fur seals (Arctocephalus gazella) arrive to the coasts of Antarctic continent to breed. Occasionally, some individuals die on the beach and their bodies are covered by snow, keeping them frozen for months. The aim of this work is to communicate the post-mortem findings in an Antarctic fur seal in the Antarctic Specially Protected Area N°132 (ZAEP 132), Island May 25/King George, South Shetland Islands, Antarctica. The results provide data on the anatomy of the species and also report the presence of a pericardial effusion.\n